A Systematic Approach to Standardizing Drinking Outcomes From Timeline Followback Data - Christina Marini; Nicole S Northover; Noah D Gold; Ursula K Rogers; Kelley C O'Donnell; Babak Tofighi; Stephen Ross; Michael P Bogenschutz (SAGE Publishing, 2023)
Objective: The timeline followback (TLFB) interview is the gold standard for the quantitative assessment of alcohol use. However, self-reported "drinks" can vary in alcohol content. If this variability is not accounted for, it can compromise the reliability and validity of TLFB data. To improve the precision of the TLFB data, we developed a detailed standard operating procedure (SOP) to calculate standard drinks more accurately from participant reports. Method: For the new SOP, the volume and alcohol content by volume (ABV) of distinct types of alcoholic beverages were determined based on product websites and other reliable sources. Recipes for specific cocktails were constructed based on recipes from bartending education websites. One standard drink was defined as 0.6 oz (14 g) of absolute alcohol. Standard drink totals were contrasted for the new SOP approach and the standard procedure, which generally assumed that one self-reported drink was equivalent to one standard drink. Results: Relative to the standard TLFB procedure, higher numbers of standard drinks were reported after implementing the TLFB SOP. Conclusions: Variability in procedures for conversion of self-reported alcohol consumption to standard drinks can confound the interpretation of TLFB data. The use and reporting of a detailed SOP can significantly reduce the potential for such inconsistencies. Detailed and consistent procedures for calculation of standard drinks can enhance the quality of TLFB drinking data.